Nutritional composition dataset of approved infant formula powder in China (2017-2024)Dataverse - Jun Cai; Shuguang Li; Qing Wei; Hong Wang; Yaguang Jiang; Jiao Jiao (Data in Brief)
Infant formula powder, mimics the composition of breast milk, is specially processed and formulated to meet the nutritional needs of infants aged 0 to 6 months. In this context, China has established a stringent registration-based regulatory system for infant formula products, requiring mandatory pre-market approval and comprehensive evaluation of all formulations before commercialization. The objective of this dataset was to collect the key parameters of registration-approved infant formulas powder in China, including product nomenclature (trade name and generic name), registration identification number, validity period, nutritional composition profiles, and supplementary remarks. Additionally, it main focused on comparative profiling of nutrient content in domestic and imported products. The complete registration dossiers of 783 infant formula powder from 2017 to 2024, officially disclosed on the Special Food Information Query Platform of China's State Administration for Market Regulation (SAMR) were systematically retrieved and collected, and verified by the nutritional values on the product packing or on the websites of the different brands. The nutritional values are systematically presented for 100 kJ and 100 g of powder. The nutrient content in domestic and imported were also statistically calculated and presented. This dataset can be applied as a tool for data-driven insights for formula optimization, aligning with China's updated national standards for precise dietary management, or to assist Chinese consumers in selecting appropriate infant formula milk powder products.